Lodging resistance and feeding quality of triticale and cereal rye lines in an alpine pastoral area of P. R. China. (14th March 2022) - Yang, Yongqiang; Liu, Hancheng; Tian, Xinhui; Du, Wenhua
Abstract: Triticale (× Triticosecale Wittmack) is a hybrid progeny of wheat ( Triticum spp.) and rye ( Secale cereale L.) and exhibits significant heterosis compared with its parents. Triticale is grown in many countries as a forage crop and has broad application prospects. In this study, conducted in 2015 and 2016 at Gansu, P. R. China, the morphological characteristics of stems, the microstructural features of the second internode from the base, and the chemical components of two triticale lines and two rye lines were compared. This study found that the plant height of triticale was lower than that of rye ( P  < .01), whereas the triticale internode diameter was larger ( P  < .05). Compared with values in rye, the diameter of the second internode from the base, thickness of the stem wall, ratio of the length of the second internode to the total length, and the sheath/internode weight ratio were all greater in triticale. Examination of the anatomical structure of the second internode revealed that the basic and vascular tissues of stems of triticale were more developed than those of rye. In addition, cellulose, lignin, neutral detergent fiber, acid detergent fiber, and ash contents of triticale stems were less than those of rye, whereas the triticale soluble sugar content was greater ( p  < .01). Therefore, we inferred that triticale stems have greater nutritional value, palatability, lodging resistance, and production potential than rye and were suitable for planting and popularizing in alpine pastoral areas. Core Ideas: From the structural features of the stems, triticale lines had strong resistance to lodging. From the chemical components of the stems, triticale lines had the higher feeding value. Two triticale lines had greater palatability and more energy.